2011
DOI: 10.3920/bm2011.0027
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic bacterial strains differentially modulate macrophage cytokine production in a strain-dependent and cell subset-specific manner

Abstract: Gut mucosal macrophages play a pivotal role in driving mucosal immune responses, resulting in either activation of inflammatory immune responses to pathogenic challenge or tolerance to beneficial luminal contents such as food and commensal bacteria. Macrophage responses elicited are dependent on tissue environment and the resulting cell subset, where homeostatic macrophages resemble the M2 macrophage subset and inflammatory macrophages resemble M1s. Probiotics can modulate macrophage function with outcome depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 43 publications
(44 reference statements)
2
42
0
1
Order By: Relevance
“…In contrary, Salinas et al (2008a) have earlier reported that L. delbrueckii induced apoptosis in teleost fish cell lines. Thus, the inhibitory effect of probiotics against pathogens may be strain specific (Habil et al, 2011). Therefore, each probiotic candidate needs to be screened in-vitro and in-vivo before being employed as dietary supplements in aquaculture practice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrary, Salinas et al (2008a) have earlier reported that L. delbrueckii induced apoptosis in teleost fish cell lines. Thus, the inhibitory effect of probiotics against pathogens may be strain specific (Habil et al, 2011). Therefore, each probiotic candidate needs to be screened in-vitro and in-vivo before being employed as dietary supplements in aquaculture practice.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that MIMLh5 bacterial cells could be more prone to induce an anti-inflammatory response in this cellular system than U937 cells and BMDMs. Such different behavior can be explained by considering that different immune responses can be induced by the same stimulus depending on the cell type, origin, and polarization (70). Moreover, because BMDMs and U937 cells have been maturated in vitro, it is plausible that they are less physiological than PCMs and that they could not possess all the features of matured macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al [11] showed that live and heat-killed LGG are able to exert similar effects on the secretion of pro- and anti-inflammatory cytokines and chemokines when included in the diet of infant rats. However, these beneficial effects have been associated with only a limited number of strains, and other strains and species cannot be presumed to exert the same effects [12, 13]. The immune effects of probiotic bacteria have therefore been shown to be extremely diverse and strain-dependent in addition to cell type-specific.…”
Section: Introductionmentioning
confidence: 99%